Factors Influencing Sleep Quality of Nursing Students - Daryaswanti, Putu Intan; Pendet, Ni Made Diah Pusparini; Febianingsih, Ni Putu Eka; Widyanata, Komang Agus Jerry; Artawan, I Kadek; Putra, I Gede Yudiana (YCAB Publisher, 2025)
Background: The transition from conventional face-to-face learning to online learning during the pandemic triggered stress in nursing students, which ultimately led to sleep disorders. Fear and anxiety due to uncertain situations also contribute to low-quality sleep among them. Objective: This study aims to determine factors related to sleep quality in nursing students during the pandemic. Method: This research was an analytical observational study with a cross-sectional design. A purposive sampling technique was applied to select 422 nursing students as research participants. In this study, sleep quality was a variable. We used the Pittsburgh Sleep Quality Index questionnaire to measure the sleep quality of nursing students. We used univariate tests to describe nursing students' characteristics, and multivariate tests with multiple regression were used to identify the factors influencing sleep quality. Results: Based on the research characteristics, the majority (94.1%) of respondents were aged 15–25, 79.1% were female, and 40.7% had nursing education. The data analysis results showed that most nursing students in Bali have poor sleep quality (97.45%). This study found that the risk factors influencing sleep quality include gender, students studying and working, anxiety, drinking coffee and soda, and noisy environments (R square 27%, F=10.236). Conclusion: These findings will provide sufficient health promotion activity strategies to improve sleep quality among nursing students. Health education involves reducing habits that can improve poor sleep quality. Keywords: nursing student; online learning; sleep quality; Bali; Indonesia